Applying Cooperative Learning to Improvestudents’ Activeness in Writing Descriptive Text - Efriyenty Efriyenty; Hermawati Syarif; Yenni Rozimela (International Journal of Educational Dynamics, 2020)
The aim of the research were to explain how cooperative learning improved student’s activeness and the factors influence students’ activeness in writing descriptive text at the grade VII students of SMPN 8 Padang. The research was Classroom Action Research. The data were collected through observation , field note, writing task and test score. The students were asked to decribe people by giving outline and describe animals based on the pictures given. The finding showed that (1) Cooperative Learning improved students’ activeness in writing Descriptive Text. It was really effective in motivating and encouraging students to be actively involved in teaching and learning process.(2) This research also revealed that there were two factors inluence students’ activenes.The factors involve teacher personal aproach and teacher motivation.